FRI0392 EVIDENCE BASED RECOMMENDATIONS FOR THE MANAGEMENT OF ENTEROPATHIC ARTHRITIS: A RHEUMATOLOGY, GASTROENTEROLOGY COLLABORATIVE INITIATIVE. (June 2019) - Hatemi, Gulen; Akar, Servet; Akpinar, Hale; Atagündüz, Pamir; Bengi, Goksel; Can, Gerçek; Celik, Aykut Ferhat; Esatoglu, Sinem Nihal; Gerçik, Önay; Hamzaoglu, Hulya; Inanc, Murat; Kabacam, Gokhan; et al.
Abstract : Background: Management of enteropathic arthritis may be challenging due to differences in treatment response of inflammatory bowel diseases and arthritis to different therapeutic modalities, which may even cause worsening of some manifestations while improving others. Enteropathic arthritis was not addressed in the management recommendations for spondyloarthritis. Objectives: The aim of this project was to develop a set of evidence based recommendations for the management of patients with enteropathic arthritis. Methods: A task force was formed that included ten rheumatologists and 8 gastroenterologists. Research questions were determined using a Delphi approach. A systematic literature search, data extraction, and statistical analyses were performed according to a pre-specified protocol. Studies that assessed the efficacy of an intervention on inflammatory bowel disease related outcomes and/or spondyloarthritis relates outcomes in patients with enteropathic arthritis were included. Risk ratios were calculated for binary outcomes and mean difference for continuous outcomes, whenever possible. Results of the systematic literature review were presented to the experts and recommendations were formulated after thorough discussions and voting. Results: A total of 4 overarching principles and 10 recommendations were formulated. The recommendations addressed the use of NSAIDs, corticosteroids, sulfasalazine and 5-ASA derivatives, TNF inhibitors, tofacitinib, secukinumab, ustekinumab and vedolizumab among patients with active inflammatory bowel disease, active arthritis, active disease regarding both inflammatory bowel disease and arthritis, and among patients in remission. Final voting showed good agreement among the group on all recommendations. Conclusion: These recommendations are intended to help rheumatologists, gastroenterologists and other clinicians dealing with enteropathic arthritis and to point out to the shortcomings of the available data on the management of this challenging condition. Disclosure of Interests: Gulen Hatemi Consultant for: Abbvie, Amgen, BMS, Janssen, MSD, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BMS, Jansen, MSD, Pfizer, UCB, Servet Akar Grant/research support from: MSD, Abbvie, Roche, UCB, Novartis, Pfizer, Amgen, Consultant for: MSD, Abbvie, Roche, UCB, Novartis, Pfizer, Amgen, Speakers bureau: Pfizer, Hale Akpinar: None declared, Pamir Atagündüz: None declared, Goksel Bengi: None declared, Gerçek Can: None declared, Aykut Ferhat Celik: None declared, Sinem Nihal Esatoglu: None declared, Önay Gerçik: None declared, Hulya Hamzaoglu: None declared, Murat Inanc: None declared, Gokhan Kabacam: None declared, Ismail Hakkı Kalkan: None declared, Levent Kılıç: None declared, Fatos Onen: None declared, Ahmet Tezel: None declared, Murat Toruner: None declared, Sedat Kiraz: None declared